2020
DOI: 10.18632/aging.103533
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the vocational and psychological perceptions and issues of transdisciplinary nurses during the COVID-19 outbreak

Abstract: Background: Due to its high infectivity and concealment, the coronavirus disease 2019 (COVID-19) outbreak that occurred in Wuhan attracted global attention. A special nursing group of transdisciplinary nurses (TNs) who had not worked in respiratory medicine, infection departments, or emergency and intensive medicine but who accounted for a large proportion of all nurses also drew our attention. Few studies have examined this special group of TNs. Therefore, this study collected the experiences and views of TNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 39 publications
3
76
0
6
Order By: Relevance
“…Nurses in COVID-19 wards had higher self-reported rates of stress, exhaustion, and depression and lower job fulfillment than nurses in non-COVID wards, 27 nurses with more work-hours and more night shifts experienced more fatigue, 28 and nurses without intensive care unit (ICU) experience deployed to COVID-19 ICUs experienced more stress. 29 Physical and mental fatigue have been associated with anxiety, depression and stress in nurses as well. 28 One study in Turkey surveyed nursing students before and after the outbreak and found that over half of the nursing students reported anxiety, and anxiety was associated with negative perspectives on the nursing profession as well as unwillingness to practice the profession of nursing in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses in COVID-19 wards had higher self-reported rates of stress, exhaustion, and depression and lower job fulfillment than nurses in non-COVID wards, 27 nurses with more work-hours and more night shifts experienced more fatigue, 28 and nurses without intensive care unit (ICU) experience deployed to COVID-19 ICUs experienced more stress. 29 Physical and mental fatigue have been associated with anxiety, depression and stress in nurses as well. 28 One study in Turkey surveyed nursing students before and after the outbreak and found that over half of the nursing students reported anxiety, and anxiety was associated with negative perspectives on the nursing profession as well as unwillingness to practice the profession of nursing in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore they experienced more perceived stress and less social support when treating patients with COVID-19. 28 In addition, our research population came from a particular hospital in Wuhan where the COVID-19 epidemic first broke out, and more medical workers died there due to infection compared with all other hospitals. Chinese and even the world media focused on workers’ status in this hospital during the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other groups, HWs have had to work longer hours under intense pressure. Increasing confirmed and suspected cases, heavy workloads, shortages of personal protective equipment, information overload, demand for specific drugs, and a lack of public support are all possible contributors to the psychological burdens faced by HWs (Fan et al, 2020;Galehdar et al, 2020;Liu Q. et al, 2020). For example, the Chinese government sent more than 42,000 HWs to treat patients in the affected areas of Hubei Province (Yao and Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%